Alimentación en Melanophryniscus stelzneri (Anura: bufonidae) - Filipello, Ana María (1994)
The alimentary categories of a population of Melanophryniscus stelzneri are studied cuantitatively and cualitatively utilizing a sample of 57 specimens obtained from "El Trapiche", province of San Luis, Argentine, in order to know the grade of trophic overlap and predation strategies. The main alimentary categories for males and females are: Formicidae, Collembola, Acari, Coleoptera, Isoptera and larvae. Although the diets of both sexes show a high grade of trophic overlap, males and females differ in the amount of each resource used. Adults and juveniles present a low grade of trophic overlap. The juveniles follow the "widely foraging" strategy and the adults follow an intermidiate one, between "sit and wait" and "widely foraging".